Use of sarolaner in the treatment of tungiasis in naturally infested dogs - Tortoriello, Rafaella; Lopes, Natália Lôres; Linhares, Bianca Bianco Paschoalino; Correia, Thais Ribeiro; Fernandes, Julio Israel (Brazilian Journal of Veterinary Medicine, 2024)
Tungiasis is an endemic dermatological parasitic zoonosis in Latin America, caused by the sand flea Tunga spp. (Siphonaptera, Tungidae), which promotes intense discomfort, swelling, erythema, itching, pain, secondary bacterial infection, cellulitis and necrosis. Sarolaner has been used to control different ectoparasites, but there is no record of its use for the treatment of tungiasis in dogs. The objective of this study was to evaluate the effectiveness of sarolaner for the treatment dogs naturally infested by Tunga spp. kept in the same infested environment. Three of four animals were medicated with sarolaner orally with a single dose of 2 mg/kg, as recommended by the manufacturer, and one animal remained without medication. After 24 hours, the fleas from all four dogs were mechanically removed. The animals were reevaluated on days +15 and +30 to assess possible reinfestation. The medicated animals remained free of fleas, while the untreated animal had fleas on the days previously defined for reevaluation. We can thus conclude that the use of sarolaner is an effective choice for tungiasis treatment.